Resistance Analysis of a Fishing Vessel with a Dihedral Bulbous Bow and Retractable Bow Foil Variations - Muhammad Al Jabbar; Dr. Fajri Ashfi Rayhan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2026)
Optimizing fishing vessel hull design is crucial for improving energy efficiency and meeting stringent environmental regulations. This study investigates the hydrodynamic resistance of a fishing vessel equipped with a dihedral bulbous bow and retractable bow foils, NACA 0015 and NACA 2408. Computational Fluid Dynamics (CFD) simulations based on Reynolds-Averaged Navier-Stokes (RANS) equations were conducted in calm water conditions. Contrary to the targeted resistance reduction, the baseline hull without foils exhibited the lowest total resistance across all tested velocities, recording 9.78 N at 1,286 m/s. Integrating the retractable foils increased total resistance by 27.48% (NACA 0015) and 15.23% (NACA 2408). This resistance penalty stems from an expanded wetted surface area amplifying frictional resistance, combined with interference resistance that disrupts the bulbous bow's streamline flow. Ultimately, the objective of a ?10% resistance reduction was unachieved, establishing the unmodified baseline hull as the most hydro-dynamically efficient configuration.